MODEL PEMBIAYAAN MUDHARABAH PADA PINJAMAN MODAL MELALUI APLIKASI OLEH PT AMARTHA MIKRO FINTECH - Sukma Putri Dertiyana; Maryati Bachtiar; Meriza Elpha Darnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
PT Amartha Micro Fintech comes with the aim of increasing UMKMthrough a group of underprivileged women by providing financing services aimedat business capital. The financing provided by Amartha to the underprivilagedwoman’s group uses sharia principles with a mudharabah. In Beringin MakmurVillage, especially the Amartha Beringin assembly, only 5 out of 30 customerscarry out their obligations using financing for business capital, even though thisprovision has been stated in Article 1 paragraph (4) of the Funding Agreement –Special Requirements of PT Amartha Micro Fintech, Article 1paragraph (11) ofLaw Number 20 of 2008 Concerning Mikro, Small, and Medium Enterprises, andNational Sharia Council Fatwa on Mudharabah (Qiradh).This type of research is empirical juridical research, while the pupulationand sample are PT Amartha Micro Fintech Pangkalan Kuras Branch and thecustomers of the Amartha Beringin assembly in Beringin Makmur Village. Thepurpose of this research is to find out the obligation of customers to use thefinancing received as business capital which aim to increase Micro, Small, andMedium Enterprises (UMKM).The conclusion of this research is the obligation of PT Amartha MicroFintech customers, especially the Amartha Beringin assembly, has not beenmaximizes due to several factors from the customer’s side as well as from the sideof field officers. The weak economic situation of customers is one of the obstaclesfor customers to establish a business through capital loans given and the largetarget that must be achieved by field officers also result in giving loans tocustomers even though they do not meet their obligations optimally. The author’sadvice for customers is given socialization related to rights and obliggations aswell as literacy to improve the business that is being run and balanced withregular monitoring of customers after the disbursement of financing.Keywords: Model – Mudharabah Financing – Application – Capital Loan.